ANALISIS KESULITAN BELAJAR SISWA PADA PEMBELAJARAN PKN DI SD NEGERI 69 BANDA ACEH - Br Ginting, Novita Anggraini; Nurdin, Syahidan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze students' learning difficulties in Civic Education (PKn), particularly on the topic of rights and obligations, in Grade IV of SD Negeri 69 Banda Aceh. This research employed a qualitative method with a descriptive approach. The subjects consisted of 32 fourth-grade students, while the classroom teacher served as the interview informant. Data were collected through documentation analysis and interviews and analyzed using the Miles and Huberman model. The findings showed that only 8 students achieved learning mastery, while 24 students had not yet met the minimum mastery criteria. Students experienced difficulties in distinguishing between the concepts of rights, obligations, and responsibilities. These difficulties were influenced by internal factors, such as limited conceptual understanding, and external factors, including the use of learning media. Teachers addressed these challenges by applying Problem Based Learning (PBL), using concrete learning media, and providing individual guidance